Lycopene in Tomato and Tomato-Based Products: Levels and Their Contribution to Dietary Lycopene - Olajire, A. A.; Ibrahim, A. 0.; Imeokparia, F. E. Adelowo-; Hammed, M. Abdul- (Biological Sciences - PJSIR, 2007)
Lycopene is a carotenoid that has antioxidant properties and imparts the red pigment i n some fruits and vegetables. Tomato (Lycopersicon esculentum Mill.) i s one of the predomi nant source of lycopene i n a typical Nigerian diet. This study evaluates the l ycopene contents of var i ous common ly con sumed tomatoes and tomato prod ucts and estimates i ts daily intake revel s. A rapid an d si mpl e spectrophotometric method for an a l yzi n g l ycopene content i n tomatoes and tomato prod ucts was u sed . Lycopene content i n various tomatoes and their prod u cts on a fresh wei ght basis ranged from 56 mg/kg to 371 mg/kg. Average daily dietary lycopene i ntake level s were assessed by means of food freq uency question naire and were estimated to be 33 .39 mg/day. Fresh tomatoes accounted for 54% of total l ycopen e intake. The l ycopene/(3-carotene ratio of tomato products is less than un i ty while that of fresh tomatoes is greater than un ity.